Bioengineering nisin to overcome the nisin resistance protein. Issue 3 (12th February 2019) - Field, Des; Blake, Tony; Mathur, Harsh; O' Connor, Paula M.; Cotter, Paul D.; Paul Ross, R.; Hill, Colin
Summary: The emergence and dissemination of antibiotic resistant bacteria is a major medical challenge. Lantibiotics are highly modified bacterially produced antimicrobial peptides that have attracted considerable interest as alternatives or adjuncts to existing antibiotics. Nisin, the most widely studied and commercially exploited lantibiotic, exhibits high efficacy against many pathogens. However, some clinically relevant bacteria express highly specific membrane‐associated nisin resistance proteins. One notable example is the nisin resistance protein that acts by cleaving the peptide bond between ring E and the adjacent serine 29, resulting in a truncated peptide with significantly less activity. We utilised a complete bank of bioengineered nisin (nisin A) producers in which the serine 29 residue has been replaced with every alternative amino acid. The nisin A S29P derivative was found to be as active as nisin A against a variety of bacterial targets but, crucially, exhibited a 20‐fold increase in specific activity against a strain expressing the nisin resistance protein. Another derivative, nisin PV, exhibited similar properties but was much less prone to oxidation. This version of nisin with enhanced resistance to specific resistance mechanisms could prove useful in the fight against antibiotic resistant pathogens. Abstract : Here we report that a strategy involving molecular approaches (site‐specific and site‐saturation mutagenesis) of the nisA structural gene has generated fully active variants of nisin with enhanced resistance to the nisin resistance protein. The study demonstrates the potential of molecular bioengineering to overcome the issue of lantibiotic peptide vulnerability to proteolytic breakdown by replacing the residues that serve as recognition sites for dedicated resistance proteins.